Assessment of the Dermatology Life Quality Index and Its Association with Medication Adherence among Patients with Chronic Skin Conditions: A Cross‑Sectional Study - Elmzughi, Rima; Alasmer, Nouralhuda; Daw, Sonia (AlQalam Journal of Medical and Applied Sciences, 2025)
Chronic inflammatory skin diseases significantly impair health-related quality of life (HRQoL), yet data on this impact and its relationship with medication adherence in Libya are scarce. To assess the QoL among Libyan patients with various dermatological conditions using the Dermatology Life Quality Index (DLQI) and to investigate the correlation between QoL and medication adherence. A cross-sectional study was conducted from July to September 2025 at Bir Usta Milad dermatology hospital. A total of 315 adult patients with chronic skin conditions were enrolled via convenience sampling. Data were collected using the DLQI questionnaire, with additional information on demographics, clinical characteristics, and medication adherence. Data analysis was performed using SPSS. The mean overall DLQI score was 5.17 ± 4.107, indicating a "small to moderate" effect on QoL. However, the impact varied significantly by diagnosis. Atopic dermatitis demonstrated the most profound impact on quality of life, with a mean DLQI of 13.33 ± 8.505 (p < 0.001), indicating a 'very large effect,' followed by eczema (mean DLQI: 6.67 ±3.915; p < 0.005). The most affected life domains were "symptoms and feelings" (itchiness/pain) and "embarrassment", with women reporting significantly greater embarrassment than men (p=0.021). A significant negative correlation was found between DLQI scores and medication adherence (Pearson's r = -0.201, p < 0.001), indicating that worse QoL was associated with a tendency towards reduced adherence. While 76.2% of patients reported no influence of QoL on adherence, 23.8% reported an effect, nearly evenly split between those who intensified (11.4%) and those who reduced (12.4%) their regimen. Dermatological conditions substantially impair HRQoL in the Libyan population, with the burden being diagnosis-specific. The significant correlation between poorer QoL and reduced medication adherence underscores the need for routine QoL assessment in clinical practice. Integrating the DLQI can help identify at-risk patients, enabling targeted interventions to improve both psychological well-being and treatment adherence for holistic patient care.